2019
DOI: 10.1038/s41598-019-43894-0
|View full text |Cite
|
Sign up to set email alerts
|

The HuR CMLD-2 inhibitor exhibits antitumor effects via MAD2 downregulation in thyroid cancer cells

Abstract: Hu antigen R (HuR) is indeed one of the most studied RNA-binding protein (RBP) since its fundamental role both in tumorigenesis and cancer progression. For this reason, downregulation in HuR protein levels or inhibition of HuR biological function are, nowadays, attractive goals in cancer research. Here, we examined the antitumor effects of CMLD-2 in four thyroid cancer cell lines (SW1736, 8505 C, BCPAP and K1). Indeed, CMLD-2 competitively binds HuR protein disrupting its interaction with RNA-targets. 35 μM CL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(37 citation statements)
references
References 46 publications
1
36
0
Order By: Relevance
“…For example, treatment with MS-444, an inhibitor interfering the RNA binding and trafficking of HuR, results in loss of viability and induction of apoptosis in malignant glioma cells [49]. Additionally, CMLD-2, a disruptor of interaction between HuR and mRNA targets, exerts antitumor effects in thyroid cancer cells by decreasing cell viability and increasing apoptosis [50], highlighting HuR as a promising therapeutic target for cancers. In this study, our evidence shows that circ-HuR is able to inhibit HuR expression and suppress the growth and aggressiveness of gastric cancer in vitro and in vivo, suggesting a potential therapeutic approach for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…For example, treatment with MS-444, an inhibitor interfering the RNA binding and trafficking of HuR, results in loss of viability and induction of apoptosis in malignant glioma cells [49]. Additionally, CMLD-2, a disruptor of interaction between HuR and mRNA targets, exerts antitumor effects in thyroid cancer cells by decreasing cell viability and increasing apoptosis [50], highlighting HuR as a promising therapeutic target for cancers. In this study, our evidence shows that circ-HuR is able to inhibit HuR expression and suppress the growth and aggressiveness of gastric cancer in vitro and in vivo, suggesting a potential therapeutic approach for cancers.…”
Section: Discussionmentioning
confidence: 99%
“…In non-small-cell lung carcinoma and thyroid cancer cells, CMLD-2 treatment decreases the mRNA expression of HuR or competitively binds to HuR, and thereby downregulates target mRNAs, such as Bax , Bcl-xL , and Mad2 . CMLD-2 treatment therefore increases apoptosis and decreases tumor aggressiveness [ 213 , 214 ].…”
Section: Rbps As Therapeutic Targets In Cancermentioning
confidence: 99%
“…Recently, CMLD-2, a small-agent that directly inhibits HuR protein, seems to display antitumor activity in non-small cell lung cancer (NSCLC) [ 55 , 56 ] and thyroid cancer (TC) [ 57 ]. In addition, treatment of NSCLC cell lines (such as A549, HCC827, H1299, H1975) with CMLD-2 triggered G1 phase cell-cycle arrest and apoptosis in a dose-dependent pattern, when compared to its minimal effect on normal fibroblastic cells (MRC-9 and CCD-16 cell lines).…”
Section: Hur Treatmentmentioning
confidence: 99%
“…CMLD-2 treatment also activated caspase-9 and -3 and induced PARP cleavage, reduced cell viability and induced apoptosis in TC cell lines (such as BCPAP, K1, 8505 C and/or SW1736), also affecting their migration and colony formation ability. Additionally, CMLD-2 treatment reduced the HuR target protein levels, microtubules-associated protein MAD2, which is upregulated in cancer [ 57 , 59 ]. Similarly, it was also shown that latrunculin A, an actin-depolymerizing macrolide, and a well-known myosin II ATPase inhibitor, blebbistatin, reduced the increased the HuR protein content of HCC cell lines, Huh7 and HepG2, in a time- and dose-dependent pattern.…”
Section: Hur Treatmentmentioning
confidence: 99%